AMELIORATIVE EFFECT OF NARINGENIN AGAINST ANTITUBERCULOSIS DRUGS INDUCED ALTERATIONS IN HEMATOLOGICAL PARAMETERS OF RATS - Sahu, Nisha; Mishra, Gita; Kumar Chandra, Hemeshwer; Kumar Nirala, Satendra; Bhadauria, Monika (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the present study was to evaluate the efficacy of naringenin against antituberculosis drugs (ATDs) induced alteration in hematological parameters in rats. Methods: Rats were administered with ATDs for 8 weeks (3 days/weeks) followed by naringenin at three different doses (10, 20, and 40 mg/kg) conjointly for 8 weeks (3 days/weeks) orally. After 8 weeks, animals were euthanized; blood was collected by retro-orbital sinus method for the analysis of hematological parameters. Results: The results of this study show decreased in red blood cells, hemoglobin, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, platelets, and eosinophils along with increase in the number of lymphocytes in ATDs induced rats. Treatment with naringenin encountered ATDs induced hematological parameter alteration which was evident by significant reversal in hematological indices toward control in dose-dependent manner. Conclusion: The present study concluded that ATDs exposure caused adverse effects in various blood components and conjoint treatment of naringenin reduced hematological alterations toward control due to antioxidant activity.